Photoactivated Fluorescence Enhancement in F, N‐Doped Carbon Dots with Piezochromic Behavior. Issue 25 (6th December 2019) - Jiang, Lei; Ding, Haizhen; Lu, Siyu; Geng, Ting; Xiao, Guanjun; Zou, Bo; Bi, Hong
Abstract: Photoactivation in CdSe/ZnS quantum dots (QDs) on UV/Vis light exposure improves photoluminescence (PL) and photostability. However, it was not observed in fluorescent carbon quantum dots (CDs). Now, photoactivated fluorescence enhancement in fluorine and nitrogen co‐doped carbon dots (F, N‐doped CDs) is presented. At 1.0 atm, the fluorescence intensity of F, N‐doped CDs increases with UV light irradiation (5 s–30 min), accompanied with a blue‐shift of the fluorescence emission from 586 nm to 550 nm. F, N‐doped CDs exhibit photoactivated fluorescence enhancement when exposed to UV under high pressure (0.1 GPa). F, N‐doped CDs show reversible piezochromic behavior while applying increasing pressure (1.0 atm to 9.98 GPa), showing a pressure‐triggered aggregation‐induced emission in the range 1.0 atm–0.65 GPa. The photoactivated CDs with piezochromic fluorescence enhancement broadens the versatility of CDs from ambient to high‐pressure conditions and enhances their anti‐photobleaching. Abstract : Photoactivated fluorescence enhancement in F and N co‐doped carbon dots is presented. The F, N‐doped CDs exhibit fluorescence enhancement when exposed to UV and reversible piezochromic behavior while applying increasing pressure (1.0 atm to 9.98 GPa), with pressure‐triggered aggregation‐induced emission in the range 1.0 atm–0.65 GPa.